2019
DOI: 10.1101/648329
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Widespread microbial mercury methylation genes in the global ocean

Abstract: 11Methylmercury is a neurotoxin that bioaccumulates from seawater to high concentrations in 12 marine fish, putting human and ecosystem health at risk. High methylmercury levels have 13 been found in the oxic subsurface waters of all oceans, yet only anaerobic microorganisms 14 have been identified so far as efficient methylmercury producers in anoxic environments. 15The microaerophilic nitrite oxidizing bacteria Nitrospina has been previously suggested as a 16 possible mercury methylator in Antarctic sea ice.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 49 publications
(75 reference statements)
1
34
0
Order By: Relevance
“…Nevertheless, recent studies have shown that biological Hg II methylation is in most environments performed by a variety of microorganisms, carrying the hgcA and hgcB gene cluster (Gilmour et al , ; Parks et al ; Yu et al ). An increasing number of recent studies detailed below have intended to evaluate the biotic Hg II methylation by studying the biodiversity and activity of hgcAB + microorganisms (Gionfriddo et al ; Bravo et al , a ; Bowman et al ; Jones et al ; Villar et al ). Nevertheless, it is established that net MMHg production also depends on other concomitant processes, including (1) the composition and activity of the whole microbial community that in turn modulate the activity of hgcAB + microorganisms (Bravo et al ), (2) physico‐chemistry that controls Hg II bioavailability (Schaefer and Morel ; Jonsson et al ; Chiasson‐Gould et al ), and uptake in microorganisms (Schaefer et al ), and (3) biotic and abiotic MMHg demethylation (Du et al ).…”
Section: The Mercury Problemmentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, recent studies have shown that biological Hg II methylation is in most environments performed by a variety of microorganisms, carrying the hgcA and hgcB gene cluster (Gilmour et al , ; Parks et al ; Yu et al ). An increasing number of recent studies detailed below have intended to evaluate the biotic Hg II methylation by studying the biodiversity and activity of hgcAB + microorganisms (Gionfriddo et al ; Bravo et al , a ; Bowman et al ; Jones et al ; Villar et al ). Nevertheless, it is established that net MMHg production also depends on other concomitant processes, including (1) the composition and activity of the whole microbial community that in turn modulate the activity of hgcAB + microorganisms (Bravo et al ), (2) physico‐chemistry that controls Hg II bioavailability (Schaefer and Morel ; Jonsson et al ; Chiasson‐Gould et al ), and uptake in microorganisms (Schaefer et al ), and (3) biotic and abiotic MMHg demethylation (Du et al ).…”
Section: The Mercury Problemmentioning
confidence: 99%
“…Similarly, a query of more than 3500 publicly available microbial metagenomes performed by Podar et al () unveiled the presence of hgcAB ‐like genes in sediments and in previously unsuspected environments, including invertebrate digestive tracts, thawing permafrost soils, coastal “dead zones,” soils and extreme environments. Moreover, a recent study assessing 243 metagenomes from the Tara Oceans expedition reported high abundances of hgcAB genes in 77 samples across all oceans (Villar et al ). The progress in genetics (Gilmour et al ; Parks et al ; Podar et al ; Bravo et al , a ; Liu et al ; Jones et al ) combined with recent advances in the use of stable isotopes to determine Hg II methylation rate constants in sediments (Monperrus et al ; Jonsson et al ; Bravo et al , ), lakes (Eckley and Hintelmann ), water columns and oceans (Munson et al ) as well as in sinking particles of marine and lake waters (Lehnherr et al ; Gascón Díez et al ) have demonstrated that the potential for MMHg formation in the environment is widespread across ecosystems.…”
Section: Methylmercury Formation Is Widespread In the Environmentmentioning
confidence: 99%
See 3 more Smart Citations